Energy efficiency assessment for the Antalya Region hotels in Turkey - Önüt, S; Soner, S (ELSEVIER SCIENCE SA, 2006)
The hotels in the Antalya Region of Turkey have become a major consumer of energy, water and other resources. However, at present, there are no existing guidelines for the efficient use and management of these resources. Energy management includes increasing in profitability due to the reduced operational costs and it is also a potential for improved market share. Many different evaluation models have been published in energy management literature. However there have been not so many systematic approaches to compare the relative efficiency of the systems. Data envelopment analysis is a special linear programming model for deriving the comparative efficiency of multiple-input multiple-output decision-making units. An evaluation of energy efficiency in 32 five-star hotels in the Antalya Region has been carried out and the results are discussed in this paper. According to this study eight hotels are efficient and twenty-four hotels are inefficient. Also for these 24 inefficient hotels, ideal energy consumptions (electricity, water and liquefied petroleum gas consumptions) are proposed to become efficient these hotels. In this study data envelopment analysis models are evaluated by using a linear programming package LINGO 5.0. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: energy efficiency; data envelopment analysis; tourism sector; HONG-KONG; PERFORMANCE; CHILLERS; Construction & Building Technology; Energy & Fuels; Engineering